Electrolyte‐Dependent Electrode Potentials in Lithium–Sulfur Batteries - Fritz Wortelkamp; Christian Wittekind; Lilli Busch; Ingo Krossing (ChemElectroChem)
Lithium–sulfur batteries are promising for future energy storage due to their high specific capacity. However, challenges like low cycling stability and the shuttle effect hinder their practical use. A better understanding of the underlying processes is crucial. This study examines the correlation between lithium potential (ELi) and sulfur reaction potentials, referenced against the ferrocenium/ferrocene couple as an (almost) solvent‐independent reference. Sulfur reactions are divided into two main stages during discharge and charge. Most sulfur reactions show a good linear correlation with ELi (R2 up to 0.87), except for the initial reduction of S8 to Li2S8, which shows no significant correlation. This suggests electrolyte design should address individual sulfur reactions rather than treating them collectively. Additionally, the correlation between ELi and the Raman‐active symmetric S–N–S stretching mode vs(SNS) in the Li[N(SO2CF3)2] electrolyte anion is analyzed across different electrolyte mixtures. A good linear correlation (R2 = 0.73) indicates that both the Raman peak position and ELi reflect the strength of the interaction between Li+ and the electrolyte solvent and hence the Li+ ion activity. These findings provide valuable insights for optimizing lithium–sulfur battery electrolytes.